Sustainable development: Adequate paradigm for humanity? - Dalia Plata de Plata (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2003)
Sustainable development, democracy, human rights in balance with the environment are the key elements that will prevail over societies and planetary continuity in the future. However, Sustainable Development (SD) requires educating the population through all possible means. This education involves promoting environmental culture materialized in the rational administration of natural resources not only for present generations but also future ones. The (SD) is not a mechanical model that any society can assume and have an environment in optimal conditions to live, it is to begin to develop it through Environmental Education in a formal way, in the classrooms of schools and universities and even in informally when collaborating with recycling campaigns, but that is not all, it is obtaining environmental sensitivity from reading the ingredients of the foods that are going to be consumed to acquiring refrigeration systems that do not damage the ozone layer and above all teaching it to children and to be able to have a clean and livable environment in the future.